Economic Feasibility Study of Emerald Hotel in Pangandaran - Immanuel, Bernhard; Aliludin, Arson (Journal of Business and Management, 2016)
Abstract. The purpose of this research is to analyze the feasibility of Emerald Hotel which located in Pangandaran, West Java. Pangandaran Beach tourism has been improving from year to year so that the high quality accommodation to retain the tourist is needed. However, there is a lack of availability of this accommodation that can result in loss of potential tourist due to switch to another tourism object and the feasibility study of the hotel in economic aspect had not been conducted. This research is to know whether this project is feasible or not and to give a recommendation what step must be conducted to make the project more profitable. This research will explain comprehensively start from the background of the problem, the objectives of the research, concept which is used in this research based on financial books and websites, the systematic method in develop the research, data collection method, detail calculation in order to catch project's Net Present Value, Internal Rate of Return, and Payback Period until give conclusion and recommendation for the project. The conclusion of this project based on data calculation in this research is Emerald Hotel project is feasible to do. The result of Net Present Value is Rp 34,013,249,479 which is greater than zero, Internal Rate of Return is 36.15% which is greater than WACC (11.25%) as hurdle rate, and Payback Period for 3 years 2 months.Keywords: Feasibility Study; Net Present Value; Internal Rate of Return; Payback Period